Medical Sentiment Analysis Using Social Media - Das, Spandan; Sharma, Aditya; Madhavan P (International Journal of Psychosocial Rehabilitation, 2020)
With the increase in the popularity of Internet, many people have created social forums to share and obtain information about medical issues concerning them or their loved ones. These forums contain experiences of people who have dealt with or are dealing with health related problems and may present some insight regarding medicines, diagnosis and treatment or interact with people with similar conditions on the forums. Observing social media forums has excited medical natural language processing analysts to uncover various cathartic anomalies. In this paper, we present a benchmark setup to analyze the sentiment with respect to people’s medical conditions considering the information, especially the information available on social medical forums. To pursue this, we requested the data from IIT Patna, who in turn collected the data from the website ‘patient.info’. The focus is given on the identification of multiple forms of medical sentiments which can be assessed from people’s medical condition and medication.